2018
DOI: 10.1002/slct.201702900
|View full text |Cite
|
Sign up to set email alerts
|

On the Influence of Substitution Patterns in Thioether‐Based Luminophores with Aggregation‐Induced Emission Properties

Abstract: In this work we present a full study on the influence of substitution patterns in aromatic thioether-based luminogens with aggregation induced emission properties. To this end nine different compounds, either with nitrile groups in ortho, meta or para positions as well as phenol groups in different positions were synthesized and investigated concerning their photophysical properties. Besides that, eight compounds were obtained as single crystals for X-ray analysis to get a deeper understanding on the packing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Furthermore, it was found that the emission of the dispersed aggregates is strong in the blue to blue‐green region of the electromagnetic spectrum ( λ em =438–481 nm), depending on the substitution pattern and in good agreement with a related study …”
Section: Resultssupporting
confidence: 89%
“…Furthermore, it was found that the emission of the dispersed aggregates is strong in the blue to blue‐green region of the electromagnetic spectrum ( λ em =438–481 nm), depending on the substitution pattern and in good agreement with a related study …”
Section: Resultssupporting
confidence: 89%
“…As an example of an active functional dye, ATE was coupled with the CuAAC reaction to the nanoparticle surface. This molecule shows aggregation‐induced emission (AIE), when the solvent contains more than 30 % H 2 O. This is reversible when DMSO content exceeds 70 % again.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore we were able to tune the emission properties from blue to red as well as the fluorescence lifetime which can be extended to up to 5μs leading to a phosphorescence emitter. This class was already used for applications in “bio”‐supramolecular chemistry such as the recognition of cell compartments in HeLa cells, the detection of specific bacterial strains as well as the formation of fluorescent supramolecular architectures . Here we describe a novel system based on our aromatic thioethers for the specific detection of bioamines.To this end we synthesized two different compounds bearing either one or two sulfonate groups which are able to recognize amines via electrostatic interactions (Figure ).…”
Section: Figurementioning
confidence: 99%